A combined dial-a-ride and fixed schedule ferry service for coastal cities. (November 2021) - Aslaksen, Ingvild Eide; Svanberg, Elisabeth; Fagerholt, Kjetil; Johnsen, Lennart C.; Meisel, Frank
Abstract: As large cities continue growing, the pressure on public transportation system increases. Water transit infrastructure has gained increased interest for coastal cities in the last years as it presents great potential for reducing congestion on urban road networks. Furthermore, the evolution of autonomous ferry systems enables more frequent departures, shorter detours, and on-demand services with many smaller ferry units operating without captain and crew on board. While most of current ferry passenger transportation systems operate on fixed scheduled routes non-autonomously, in the last decades, there has been an increased interest in on-demand public transit services as these provide more flexibility and customized services. This paper investigates the potentials of combining fixed schedule and on-demand ferry services. For this, we present a request assignment procedure and a ferry routing methodology that are embedded in a simulation framework. Through this, we examine the impact of fleet composition (i.e., number of scheduled and on-demand ferries) on the fulfilled customer demand and the service times of requests. Our computational experiments evaluate the relation between fleet size and fleet composition under various demand scenarios for a case study of the coastal city Kiel, Germany.